Women’s appraisal of the management of vulvodynia by their general practitioner: a qualitative study - Leusink, Peter (Fam Pract, 2019)
BACKGROUND: Provoked Vulvodynia (PVD) is the most common cause of vulvar pain. General practitioners (GPs) are insufficiently familiar with it, causing a delay in many women receiving correct diagnosis and treatment. Besides patients factors, this delay can partly be explained by the reluctance of GPs to explore the sexual context of PVD and by their negative emotional reactions such as helplessness and frustration when consulted by patients with medically unexplained symptoms like PVD. OBJECTIVE: To gain insight into how women with PVD perceive and evaluate condition management by their GP, in order to support GPs in the consultation of women with PVD. METHODS: We performed face-to-face in-depth interviews with women diagnosed with PVD. The interviews were recorded, transcribed verbatim and thematically analysed. The Consolidated Criteria for reporting Qualitative Research (COREQ-criteria) were applied. RESULTS: Analysis of the interviews generated four interrelated themes: Doctor-patient relationship, Lack of knowledge, Referral process and Addressing sexual issues. Empathy of the GP, involvement in decision-making and referral were important factors in the appreciation of the consultation for women with PVD who were referred to a specialist. Because women were reluctant to start a discussion about sexuality, they expected a proactive attitude from their GP. The communication with and the competence of the GP ultimately proved more important in the contact than the gender of the GP. CONCLUSION: Women with PVD prefer a patient-centred approach and want GPs to acknowledge their autonomy and to address sexuality proactively.